Factors Contributing to Malnutrition in Parkinson's Disease Patients With Freezing of Gait - Zhang, Li-Li; Zhang, Liang; Dong, Jingde; Zhao, Ying; Wang, Xiao-Ping (Frontiers in Neurology, 2022)
Background and Purpose: Little is known about the nutritional status and clinical characteristics of patients with Parkinson's disease with freezing of gait (PDFOG). The purpose of this study was to describe the relationship between nutritional status and characteristics of patients with PDFOG. Methods: In this cross-sectional study, 178 PDFOG patients were recruited and classified as nutritionally normal or at risk of malnutrition/already malnourished based on their Mini Nutritional Assessment (MNA) scores. Each participant underwent a structured questionnaire, physical examination and routine serum biochemical tests. Results: We found that 44.4% and 37.1% of PDFOG patients were malnourished [mini nutritional assessment (MNA) score <17] and at risk of malnutrition (17 ≤ MNA score ≤23.5), respectively. Compared to patients with normal nutrition, PDFOG patients with malnutrition and at risk of malnutrition had longer duration of Parkinson's disease (PD) and freezing of gait (FOG), more levodopa equivalent daily doses (LEDD), lower body mass index (BMI), more motor symptoms according to the Unified PD Rating Scale-III (UPDRS-III) and non-motor symptoms according to the PD Non-motor Symptoms Questionnaire (PD-NMS) (P < 0.05). Uric acid, albumin, prealbumin, and total cholesterol (TC) differed between the two groups (P < 0.05). High Hoehn and Yahr (H-Y) stage, high Freezing of Gait Questionnaire (FOGQ) scores, low TC and low uric acid were risk factors for malnutrition in patients with PDFOG. Conclusion: Our results showed disease severity, motor symptoms, TC levels and uric acid levels were all associated with nutritional status in patients with PDFOG. This study suggest early discovery of the nutritional status of PDFOG patients is important.